Teachers’ View of the Difficulty of Selected Environmental Concepts in Primary School Textbooks - Pavlátová, Věra; Kroufek, Roman (Scientia in educatione, 2018)
The article seeks to identify those environmental concepts which may pose a problem when being integrated into the knowledge structures of elementary school pupils. Based on the presence of these concepts in curriculum documents, especially in textbooks, of most of the primary and lower-secondary school grades, 20 were selected according to predetermined criteria. The concepts fall into the area of environmental education (EE); they appear in primary and lower-secondary school curricula; they had been consulted with both methodologists and educators; they are either among the key concepts of environmental education, or difficulties in understanding them can be anticipated; connections can be found between them. We present the assessment of these concepts as they are perceived by both beginning and experienced teachers (N = 60) of both primary and lower-secondary school levels, in terms of their difficulty for pupils and possible misconceptions. The respondents evaluated each concept on the five-level Likert scale and also verbally. When comparing the responses of the primary and lower-secondary teachers, the number of points attributed to each individual concept was summed up, with the resulting sum characterizing the construct of the “perception of the difficulty of the concept” by an individual teacher. The reliability of the research tool was sufficient (α = 0.89). The study established that the length of the teachers’ practice only had a minor influence on the studied construct (r = 0.32, p < 0.001). The difference in the perception of the researched concepts among the primary and lower-secondary teachers was not proven (p = 0.19). The final analysis then taxonomizes the concepts into three categories, the easily understandable, understandable and difficult to understand, and compares the results with other relevant research. The article also discusses possible reasons why the teachers might have chosen the particular concepts, and outlines other research directions related to this issue.